2017
DOI: 10.1186/s12885-017-3255-z
|View full text |Cite
|
Sign up to set email alerts
|

Sidedness is prognostic in locoregional colon cancer: an analysis of 9509 Australian patients

Abstract: Background/AimRight sided colon cancer (RsCC) is proposed to be a distinct disease entity to left sided colon cancer (LsCC). We seek to confirm primary tumour location as an independent prognostic factor in locoregional colorectal cancer.MethodsAll patients with stage I – III primary adenocarcinoma of colon were identified from the New South Wales (NSW) clinical cancer registry (2006–2013). Primary tumour location (RsCC vs LsCC) survival analyses were conducted using the Kaplan-Meier method, and adjusted hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 30 publications
3
38
0
2
Order By: Relevance
“…These authors included patients with nonmetastatic colon tumors in the analysis and observed that patients with right‐sided colon tumors and clinical stages (CS) III and IV had worse survival whereas those with right‐sided colon tumors at CS I and II did not have significant differences in survival. A large Australian case series (9509 patients) included only nonmetastatic disease and had similar findings, with lower survival among patients with right‐sided colon tumors and CS III . Other studies that included patients with nonmetastatic disease obtained different results for patients with CS I and II.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…These authors included patients with nonmetastatic colon tumors in the analysis and observed that patients with right‐sided colon tumors and clinical stages (CS) III and IV had worse survival whereas those with right‐sided colon tumors at CS I and II did not have significant differences in survival. A large Australian case series (9509 patients) included only nonmetastatic disease and had similar findings, with lower survival among patients with right‐sided colon tumors and CS III . Other studies that included patients with nonmetastatic disease obtained different results for patients with CS I and II.…”
Section: Introductionmentioning
confidence: 74%
“…A large Australian case series (9509 patients) included only nonmetastatic disease and had similar findings, with lower survival among patients with right-sided colon tumors and CS III. 10 Other studies that included patients with nonmetastatic disease obtained different results for patients with CS I and II. However, these studies have consistently demonstrated the negative impact of rightsided colon tumors in patients with CS III.…”
mentioning
confidence: 99%
“…However, the subgroup analysis showed a significant better survival in stage III LCC (HR, 1.12; 95% CI, 1.06‐1.18; P < 0.001), but worse survival in stage II LCC (HR, 0.92; 95% CI, 0.87‐0.97; P = 0.001) compared with RCC . The discrepancy in the survival by stage was reported recently in both Eastern and Western countries . Despite variation in the reported results, most authors observed a poor survival for RCC in stage III cases.…”
Section: Discussionmentioning
confidence: 82%
“…For the reasons, many authors have indicated RCC as a disease distinct from LCC. Most studies have shown that survival with RCC is poorer than that with LCC for either primary lesions or cancer with metastasis . However, these previous studies mainly analyzed patients with primary colon cancer undergoing resection or patients with metastatic colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation